Model Problem Based Learning Berbantuan Media Flipbook Terhadap Hasil Belajar Matematika Siswa SD - Safitri, Nurul; Nuriman, Nuriman; Alfarisi, Ridho; Setya, Cahyo (Universitas Negeri Surabaya, 2024)
This research aims to determine whether or not there is an influence of the PBL model assisted by flipbook media on mathematics learning outcomes regarding perimeter and area of ??flat shapes in class IV students at SDN Kranjingan 3 Jember. The research design used in this research is a quasi-experimental research design (Quasi Experiment). The data analysis technique used in this research is the t-test analysis technique. Whether or not there is an influence of the PBL model assisted by flipbook media on learning outcomes. From the research results, it is known that the PBL model assisted by flipbook media has a significant positive influence on mathematics learning outcomes regarding perimeter and area of ??flat shapes in class IV students at SDN Kranjingan 03.